Studies on the venom proteome of Bothrops asper: Perspectives and applications - Alape Girón, Alberto (2009)
Bothrops asper is responsible for the vast majority of snakebite accidents in Central America and several studies have demonstrated that specific toxic and enzymatic activities of its venom vary with the geographic origin and age of the specimens. Variability in venom proteins and enzymes between specimens from the Caribbean and the Pacific versants of Costa Rica has been reported since 1964. Recently, we performed a comparative proteomic characterization of the venoms from one population of each versant. Proteins belonging to several families, including disintegrin, phospholipases A2, serine proteinases, C-type lectins, CRISP, L-amino acid oxidase, and Zn2þ-dependent metalloproteinases show a variable degree of relative occurrence in the venoms of both populations. The occurrence of prominent differences in the protein profile between venoms from adults and newborns, and among venom samples from individual specimens of the same region or developmental stage, further demonstrated the existence of geographic, ontogenetic and individual variability in the venom proteome of this species. These findings provide new insights towards understanding the biology of B. asper, contribute to a deeper understanding of the pathology induced by its venom and underscore the importance of the use of venoms pooled from specimens from both regions for producing antivenom exhibiting the broadest cross-reactivity. Furthermore, knowledge of the protein composition of B. asper venom paves the way for detailed future structure–function studies of individual toxins as well as for the development of new protocols to study the reactivity of therapeutic antivenoms.